Dynamic light scattering optical coherence tomography to probe motion of subcellular scatterers - Arezza, Nico J. J. (J Biomed Opt, 2019)
Optical coherence tomography (OCT) is used to provide anatomical information of biological systems but can also provide functional information by characterizing the motion of intracellular structures. Dynamic light scattering OCT was performed on intact, control MCF-7 breast cancer cells and cells either treated with paclitaxel to induce apoptosis or deprived of nutrients to induce oncosis. Autocorrelations (ACs) of the temporal fluctuations of OCT intensity signals demonstrate a significant decrease in decorrelation time after 24 h in both the paclitaxel-treated and nutrient-deprived cell groups but no significant differences between the two groups. The acquired ACs were then used as input for the CONTIN deconvolution algorithm, and all produced CONTIN outputs with three distinct peaks for all experimental conditions. After 24 h of either paclitaxel treatment or nutrient deprivation, the area-under-the-curve (AUC) of the first peak increased significantly while the AUC of the third peak decreased significantly. These results lend strong support to the hypothesis that ACs acquired from cells are composed of multiple components that correspond to light scattered by different subcellular structures and organelles.